Designing Highly Photoactive Hybrid Aerogels for In-Flow Photocatalytic Contaminant Removal Using Silica-Coated Bacterial Nanocellulose Supports - Almeida da Silva, Thaís Caroline [UNESP]; Marchiori, Leonardo [UNESP]; Oliveira Mattos, Bianca; Ullah, Sajjad; Barud, Hernane da Silva; Romano Domeneguetti, Rafael [UNESP]; Rojas-Mantilla, Hernán Dario [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP]; Rodrigues-Filho, Ubirajara Pereira; Ferreira-Neto, Elias Paiva; Ribeiro, Sidney José Lima [UNESP] (American Chemical Society (ACS), 2023)
This study explores the use of silica-coated bacterial nanocellulose (BC) scaffolds with bulk macroscopic yet nanometric internal pores/structures as functional supports for high surface area titania aerogel photocatalysts to design flexible, self-standing, porous, and recyclable BC@SiO2-TiO2 hybrid organic-inorganic aerogel membranes for effective in-flow photo-assisted removal of organic pollutants. The hybrid aerogels were prepared by sequential sol-gel deposition of the SiO2 layer over BC, followed by coating of the resulting BC@SiO2 membranes with a porous titania aerogel overlayer of high surface area using epoxide-driven gelation, hydrothermal crystallization, and subsequent supercritical drying. The silica interlayer between the nanocellulose biopolymer scaffold and the titania photocatalyst was found to greatly influence the structure and composition, particularly the TiO2 loading, of the prepared hybrid aerogel membranes, allowing the development of photochemically stable aerogel materials with increased surface area/pore volume and higher photocatalytic activity. The optimized BC@SiO2-TiO2 hybrid aerogel showed up to 12 times faster in-flow photocatalytic removal of methylene blue dye from aqueous solution in comparison with bare BC/TiO2 aerogels and outperformed most of the supported-titania materials reported earlier. Moreover, the developed hybrid aerogels were successfully employed to remove sertraline drug, a model emergent contaminant, from aqueous solution, thus further demonstrating their potential for water purification.
Keywords: aerogel; bacterial cellulose; in-flow decontamination; photocatalytic membrane; SiO2; TiO2